Statistical Literacy Learning Design Using Concept Maps To Facilitate Statistical Literacy Abilities - Baharuddin, Baharuddin; Suradi Tahmir; Hisyam Ihsan (International Journal of Education, Vocational and Social Science, 2025)
Statistical literacy is an important skill that must be possessed by students, especially in the field of mathematics education, to understand and analyze data effectively. This study aims to develop a statistical literacy learning design by utilizing concept maps that meet the criteria of validity, practicality, and effectiveness. The research design used in this study is Educational Design Research (EDR). The subjects of this study involved Mathematics Education students of UIN Alauddin Makassar. The research instruments used include validation sheets, guidebooks, student worksheets, test instruments, learning modules, response questionnaires, learning design implementation sheets, and student activity observation sheets. Data analysis was carried out based on three main aspects, namely validity, practicality, and effectiveness. Hypothesis testing was carried out using the Independent sample t-test to compare student learning outcomes between the experimental class using statistical literacy learning design with concept maps and the control class using conventional learning. The results of the analysis show that this learning design is valid after going through a validation process by experts, practical based on positive responses from lecturers and students, and effective in improving student learning outcomes. The results of the hypothesis test using the Independent sample t-test showed that there was a significant difference between the experimental class and the control class, with an average value of student learning outcomes in the experimental class of 81.04, exceeding the KKM of 75, and classical completeness reaching 83.33%. Thus, the developed statistical literacy learning design has proven effective in improving students' understanding and skills in statistical literacy.